PENGUATAN KPK (KETAHANAN PANGAN KELUARGA) PADA MASA PANDEMI DI DESA SALAMKANCI - Megita Dwi Pamungkas; Rina Rahayu; Fadhilah Rahmawati (LPPM Universitas Bina Bangsa, 2021)
The purpose of this activity is to overcome the problems faced by partners, namely the lack of public awareness to use yard land to meet the food needs of families in the pandemic period. The method used in this activity is PRA (Parcitipatory Rural Appraisal). This approach engages people to understand problems and increases the participation of the community to solve their own problems. Participants of this activity are the mothers of PKK members in Salamkanci Village, Bandongan Subdistrict, Magelang Regency. The first activity is socialization that continues counseling on family food security (KPK) and KPK strengthening strategies, then given motivation and training on the use of yard land then residents are given horticultural plant seeds taken from garden seeds to practice the results of training in their respective yards. As a result, public awareness to use yard land to grow various types of plants is increasing